Does computer navigation system really improve early clinical outcomes after anterior cruciate ligament reconstruction? A meta-analysis and systematic review of randomized controlled trials. - Cheng T; Zhang GY; Zhang XL; Cheng, Tao; Zhang, Guo-You; Zhang, Xian-Long (Knee (0968-0160), 2012)
Inaccurate tunnel placement is an important cause of failure in conventional anterior cruciate ligament (ACL) reconstruction. Controversy currently exists over the usefulness of computer-assisted navigation systems in addressing this problem. Five randomized or quasi-randomized, controlled trials comparing computer-navigated versus conventional technique in ACL reconstructions until December 1, 2009 were identified through a systematical database search. The clinical outcomes of the trials were analyzed by Lachman test, pivot-shift test, International Knee Documentation Committee knee score, Lysholm score, and Tegner score. Mean difference or risk ratio with 95% confidence interval was calculated using a fixed-effects or random-effects model. Heterogeneity across the studies was also assessed. We found that the use of computer-assisted navigation systems led to additional operative time (8-17min). No significant differences between computer-navigated and conventional groups were found in terms of knee stability and functional assessment during short-term follow-up. The role of computer-assisted navigation systems on clinical performance and longevity needs further investigation in large sample, long-term randomized trials.